The EMTP and the analysis of protection against lightning impulse for a 500 KV substation - Fang, Min; Yu, Cun Yi; Surapong Chiraratananon; Malik, Arif Saeed; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1996)
To operate an electric power system reliably, a variety of network studies should be performed. Among these, studies concerned with electromagnetic transients are probably the most complicated ones. For the beginner, there is the difficulty of developing an understanding of the nature of electromagnetic transients in power systems, in addition to the difficulty of learning how to simulate them with the Electromagnetic Transients Program (EMTP). The first part of this thesis gives some advice on how to use the EMTP properly. The general knowledge of solution method, limitations and inherent errors of EMTP simulations are included as well. A substation is designed to operate satisfactorily not only under the stresses associated with the normal operating power-frequency voltage but also under those caused by transient overvoltage arising on the network. The insulation strength and characteristics of the various components of a substation must be selected relative to these stresses to reduce the frequency of supply interruptions, and particularly of component failures, to levels low enough to be both operationally and economically acceptable. In the second part of this thesis, the protection against the lightning impulse in a gas-insulated substation is analyzed. Determination of the measure of lightning surge protection needed for the substation depends on the EMTP results.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Electric substations